Single‐Step Fabrication of High‐Density Microdroplet Arrays of Low‐Surface‐Tension Liquids. Issue 16 (24th February 2016) - Feng, Wenqian; Li, Linxian; Du, Xin; Welle, Alexander; Levkin, Pavel A.
Abstract : A facile approach for surface patterning that enables single‐step fabrication of high‐density arrays of low‐surface‐tension organic‐liquid microdroplets is described. This approach enables miniaturized and parallel high‐throughput screenings in organic solvents, formation of homogeneous arrays of hydrophobic nanoparticles, polymer micropads of specific shapes, and polymer microlens arrays.